1995
DOI: 10.1200/jco.1995.13.11.2813
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric desmoid tumor: retrospective analysis of 63 cases.

Abstract: A surgical approach aiming at clear margins is presently the best treatment option. When this cannot be accomplished without severe disfigurement or function impairment, partial resection is an acceptable alternative, but one associated with a high risk of regrowth. Whether adjuvant strategies should be used in this situation remains to be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
101
2
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 25 publications
4
101
2
1
Order By: Relevance
“…8,12 Including the current analysis, 85 patients underwent primary surgery and had information available regarding surgical margin status and disease recurrence (Table 4). 5,6,8,10,12 The recurrence rate among patients with SN margins was 16%, compared with 67% among patients with SP margins. In patients with SP margins, 74% of those who did not receive additional therapy developed recurrent disease, compared with 40% of patients who received adjuvant treatment.…”
Section: Literature Reviewmentioning
confidence: 97%
See 3 more Smart Citations
“…8,12 Including the current analysis, 85 patients underwent primary surgery and had information available regarding surgical margin status and disease recurrence (Table 4). 5,6,8,10,12 The recurrence rate among patients with SN margins was 16%, compared with 67% among patients with SP margins. In patients with SP margins, 74% of those who did not receive additional therapy developed recurrent disease, compared with 40% of patients who received adjuvant treatment.…”
Section: Literature Reviewmentioning
confidence: 97%
“…None of the pediatric AF studies reported patients with familial history of AF or FAP, and only two patients with Gardner syndrome were reported. 6 In 3 studies of pediatric AF, 20% of patients (n ϭ 108 patients) had a history of local trauma before they developed AF. 5,6,8 Seven of 10 pediatric AF studies, including the current investigation, reported treatment of the primary tumor, and all patients generally underwent initial surgery (n ϭ 168 patients) ( Table 3).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Motor weakness is possible if the tumor infiltrates or encases large nerves. Rare cases of multicentric lesions have been described 7,9,14 ; in most cases, the second growth develops proximal to the primary lesion. Microscopically, deep fibromatosis is poorly circumscribed and infiltrates the surrounding tissue, usually striated muscle.…”
mentioning
confidence: 99%